An Empirical Study of Unsystematic Risk Factors in the Capital Asset Pricing Model: the Case of Russian Forestry Sector - Varvara Nazarova (Entrepreneurial Business and Economics Review, 2013)
The objective of this paper is to consider the Capital Asset Pricing Model, to determine its most disputable points, to identify concepts defining and supplementing the points of the model. The article ends with an example of calculation of the cost of equity for a company of a forestry sector of Russia.The originality of the research is based on the assessment of the effects of non-systematic risks on investment projects in the forestry sector in Russia.